Measuring Mild Cognitive Impairment in Patients With Parkinson’s Disease - Marras, Connie (Mov Disord, 2013)
We examined the frequency of Parkinson disease with mild cognitive impairment (PD-MCI) and its subtypes and the accuracy of 3 cognitive scales for detecting PD-MCI using the new criteria for PD-MCI proposed by the Movement Disorders Society. Nondemented patients with Parkinson’s disease completed a clinical visit with the 3 screening tests followed 1 to 3 weeks later by neuropsychological testing. Of 139 patients, 46 met Level 2 Task Force criteria for PD-MCI when impaired performance was based on comparisons with normative scores. Forty-two patients (93%) had multi-domain MCI. At the lowest cutoff levels that provided at least 80% sensitivity, specificity was 44% for the Montreal Cognitive Assessment and 33% for the Scales for Outcomes in Parkinson’s Disease-Cognition. The Mini-Mental State Examination could not achieve 80% sensitivity at any cutoff score. At the highest cutoff levels that provided specificity of at least 80%, sensitivities were low (≤44%) for all tests. When decline from estimated premorbid levels was considered evidence of cognitive impairment, 110 of 139 patients were classified with PD-MCI, and 103 (94%) had multi-domain MCI. We observed dramatic differences in the proportion of patients who had PD-MCI using the new Level 2 criteria, depending on whether or not decline from premorbid level of intellectual function was considered. Recommendations for methods of operationalizing decline from premorbid levels constitute an unmet need. Among the 3 screening tests examined, none of the instruments provided good combined sensitivity and specificity for PD-MCI. Other tests recommended by the Task Force Level 1 criteria may represent better choices, and these should be the subject of future research.